Knowledge management and financial performance in transitional economies: the case of Serbian enterprises - Kavalić, Mila; Nikolić, Milan; Stanisavljev, Sanja; Đorđević, Dejan; Pečujlija, Mladen; Terek Stojanović, Edit (Journal of Business Economics and Management, 2021)
In this paper the impact and predictive effects of knowledge management on financial performance are analysed. The research also includes an analysis of the moderating effects of two moderators (National Origin and Enterprise Size) and their relationship. The data was gathered by interviewing 520 managers from manufacturing companies operating in Serbia. The most important conclusions of the research are: 1. High levels of knowledge management positively influence business performance, quality and competitiveness. 2. Financial performance is mainly influenced by the dimensions connected to the effects of knowledge management regarding its implementation and protection and the acquisition of competitive advantages. 3. Knowledge management strongly influences the market aspects of business, but also the increase of fixed assets. 4. Knowledge management has a slightly greater impact on financial performance in foreign enterprises (operating in Serbia) compared to domestic (Serbian) enterprises. The situation is similar when comparing medium and large enterprises (a higher impact) with small enterprises (a smaller impact). 5. The greatest effects are achieved when an effective organizational structure is in place, when the organization protects its knowledge, when it manages to materialize the knowledge gathered in the form of the efficient application of knowledge.